Design and characterize of kirigami-inspired springs and the application in vertebrae exoskeleton for adolescent idiopathic scoliosis brace treatment - Lei, Qiwen Emma; Shu, Jing; Wang, Junming; Cheung, Hoi Yan; Cheung, Jason P. Y.; Wong, Wing Fai; Lau, Sanders Cheuk Yin; Yip, Joanne; Tong, Raymond K. Y. (Frontiers in Mechanical Engineering, 2023)
Adolescent idiopathic scoliosis (AIS) is a common condition that affects children between the age of 10 and young adulthood. Rigid brace treatment is an effective treatment to control the progression of spinal deformity. However, it limits mobility and causes discomfort, which leads to low treatment compliance. In this study, we developed and characterized a kirigami-inspired CT/MRI compatible spring that could be employed to modify our previously designed exoskeleton hinge vertebrae to provide immediate in-brace correction, good wear comfort, and one that does not inhibit mobility simultaneously. Additive manufacturing has drawn significant interest in academic and industrial terms due to its ability to produce geometrically complex structures. The structural design and dimension of the proposed 3D printed kirigami-inspired springs were optimized with the finite element method (FEM). The carbon-fiber-reinforced nylon material (PA-CF) was selected as the material of the kirigami-inspired spring with the balance of printing easiness and performance of the material. The stiffness of designed kirigami-inspired springs varied between 1.20 to 42.01 N/mm. A case series study with three scoliosis patients has been conducted to investigate the immediate in-brace effect on reducing the spinal curvature and asymmetry of the body contours using radiographic examination. The experiment results show that there are 4.6% to 50.5% improvements in Cobb angle for different sections of spines. The X-ray images proved that our kirigami-inspired springs would not block views for Cobb angle measurements.